Probing local thermodynamical properties of a nanomechanical resonator in a scanning electron microscope - Chardin, Clément (2024)
Micro and nano-mechanical devices have attracted increasing interest from scientists and engineers over the last few years because of their promising fundamental and technical applications. Their extremely low masses make them very sensitive to noises and forces, making them perfectly suited to act as detectors of weak forces or for testing new physics and potentially bringing quantumness towards the macroscopic world. Both the fabrication processes for producing nanomechanical resonators and the detection schemes used to monitor their motion have greatly improved recently. In particular, unprecedented sensitivities have been achieved with optomechanical detection systems and ultra-high mechanical quality factors.